Production of an extracellular protease by an Antarctic bacterial isolate (Bacillus sp. JSP1) as a potential feed additive - Park, Inkyung; Cho, Jaiesoon (Revista Colombiana de Ciencias Pecuarias, 2011)
Extracellular proteolytic activity was found in JSP1, an Antarctic bacterial isolate. The strain was related to Bacillus sp, based on 16S rRNA gene sequence analysis. The JSP1 protease was partially purified by ammonium sulfate precipitation. Optimal enzyme activity occurred at 40 oC and pH 7.4. Enzyme activity was significantly enhanced in the presence of Mg2+ and Ca2+ and was completely inactivated in presence of Cu2+, Zn2+, Hg2+, EDTA and SDS. The enzyme hydrolyzed casein the most effectively among the protein substrates tested. The enzyme also exhibited relatively high activity on keratin and gluten, and was active against peptidyl conjugates such as L-Leu-p-Nitroanilide and N-Succinyl-L-Phe-p-Nitroanilide. This study suggests that JSP1 protease could be utilized as a potential environmentally-friendly feed additive in animal production. Key words: antarctic, Bacillus sp., feed additive, keratin, livestock production, protease. Proteasa extracelular de un aislado bacteriano Antartico (Bacillus sp. JSP1) con uso potencial como aditivo alimenticio para animales Resumen Se reporta haber encontrado actividad proteolítica extracelular en una bacteria antártica denominada JSP1. Con base en el análisis de secuencia genética 16S ARNr, la cepa fué relacionada con Bacillus sp. La proteasa JSP1 fué parcialmente purificada por precipitación con sulfato de amonio. La actividad óptima de la enzima se produjo a 40 ºC y pH 7,4. La actividad enzimática fue significativamente mayor en presencia de Mg2+ y Ca2+ y se inactivó completamente en presencia de Cu2+, Zn2+, Hg2+, EDTA y SDS. Entre todos los sustratos ensayados, el más eficientemente hidrolizado por la enzima fue la caseína. La enzima tuvo actividad relativamente alta sobre la queratina y el gluten, y participó activamente contra conjugados peptídicos como la L-Leu-p-nitroanilida y la N-succinil-L-fenilalanina-p-nitroanilida. La enzima podría ofrecer potencial para su uso como aditivo alimenticio ecológico en producción animal. Palabras clave: antártida, aditivo alimenticio, Bacillus sp., producción animal, proteasa queratina. Produção de proteasa extracelular por bactérias antárcticas isoladas, Bacillus sp. JSP1 como um aditivo potencial em concentrado Resumo A actividade proteolítica extracelular foi encontrada a partir de uma bactéria antárctica denominada JSP1, mediante uma análises de sequencia do gene 16S rRNA, a cepa foi relacionada para Bacillus sp. A proteasa JSP1 foi parcialmente purificada por precipitação com sulfato de amônia. Uma óptima actividade enzimática ocorreu em 40 oC e pH 7,4. A actividade da enzima foi significativamente maior na presença de Mg2 + e Ca2 +, e foi completamente inactivada em presença de Cu2 + Zn2 +, Hg2 +, EDTA e SDS. A enzima hidrolisada de caseína foi mais eficaz entre os substratos de proteína testados, apresentando maior actividade na queratina e no glúten e foi activo contra os peptidil conjugados como L-Leu-p Nitroanilida e N-succinil-L-Phe-p-Nitroanilida. A enzima pode ser utilizado como aditivo ambiental na alimentação animal. Palavras chave: antarctic, Bacillus sp., feed additive, keratin, livestock production, protease.